2022
DOI: 10.1002/jca.22032
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and cost of double filtration plasmapheresis in severe hypertriglyceridemia‐induced pancreatitis: A retrospective observational study

Abstract: BackgroundThe value of double ltration plasmapheresis (DFPP) in severe hypertriglyceridemia-induced pancreatitis (sHTGP) is controversial. This study aimed to investigate the e cacy of DFPP on clinical results in patients with sHTGP and the costs associated with the procedure. MethodsPatients who underwent DFPP after admission between January 2016 and December 2021 were recruited. Data on lipid pro le, clinical results, and costs were retrospectively collected and analyzed. ResultsFifty sHTGP patients who rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Because DFPP has the advantage of reducing the need for fresh frozen plasma (FFP) as a replacement uid and signi cantly reducing the risk of allergic reactions and viral infections secondary to FFP, it has been increasingly used to treat HTG-AP in recent years [20][21][22][23][24][25][26][27] . However, there is little evidence to conclude that DFPP has an effect on improving outcomes of patients with HTG-AP, particularly in terms of reducing organ injury [22][23][24][25] . It has been reported that rapid TG clearance by DFPP in the clinical setting may not translate into a theoretical effect [26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Because DFPP has the advantage of reducing the need for fresh frozen plasma (FFP) as a replacement uid and signi cantly reducing the risk of allergic reactions and viral infections secondary to FFP, it has been increasingly used to treat HTG-AP in recent years [20][21][22][23][24][25][26][27] . However, there is little evidence to conclude that DFPP has an effect on improving outcomes of patients with HTG-AP, particularly in terms of reducing organ injury [22][23][24][25] . It has been reported that rapid TG clearance by DFPP in the clinical setting may not translate into a theoretical effect [26][27] .…”
Section: Introductionmentioning
confidence: 99%